Constraints of buffalo farming in Kallakurichi district of Tamil Nadu, India - Rajadurai, Annadurai; Alimudeen, Sirajudeen; Kumaravelu, Natarajan (Buffalo Bulletin, 2022)
A study was conducted to identify the constraints perceived by the buffalo farmers in Kallakurichi district of Tamil Nadu. For this study, data were collected from the randomly selected buffalo farmers by using a structured interview schedule. The present study indicated that the major constraints faced by buffalo dairy farmers were high cost of concentrates (63.82% Garrett score), followed by high capital investment in animal housing (53.64% Garrett score), Low conception rate (58.92% Garrett score) repeat breeding (60.20% Garrett score), lower milk price 64.34% Garrett score), Unavailability of credit facilities from government side (50.80% Garrett score), high cost involved in veterinary care (56.28% Garrett score) and reproductive disorders (48.70% Garrett score).